Planning Culture Activation Program Using Predictive Analytics: A Case Study at PT. Telkom Indonesia-TR3 - Pratami Anggina; Shandy Asri Achmad; John Welly (Institut Teknologi Sepuluh Nopember, 2020)
Being world-class company not happen by only having effective business processes or good quality and competitive products, but it's about how the company focus on the character or DNA of the company. Culture can be defined as the group’s DNA such as genes to support the autoimmune system for enhance company’s growth. Positive organization culture can boost the employee engagement. How it would be? Appropriate culture activation program should leads to what the company wants. When assign employee engagement and satisfaction dimension and attribute, authors take the model from secondary data from EES (Employee Engagement and Satisfaction) Report 2014-2018 of PT Telkom Indonesia. Human resource (HR) is a function that fight for the company success story because the company's assets are employees. Predictive analytics complements various techniques (statistics, modeling, data mining) by considering the latest facts or company strategy and historical conditions of the company to make predictions about the future. From EES Report the dimensions and attributes are processed into statistical processing as done in predictive analytics. Set engagement and satisfaction as an outcome. And the strong correlation attribute would become the key for culture activation plan that suitable with corporate strategy to enhance employee engagement. The strong correlation attribute from this statistical processing are leadership, career path, and promote product awareness. Then appropriate culture activation program should lead suitable with that strong attributes. The author assume that 95% employees can join this culture activation, therefore with use the strong predictive correlation attribute for culture activation the employee engagement would increase 8,24%, and employee satisfaction would growth 6,95% than 2018